Waste office paper filled polylactic acid composite filaments for 3D printing. (15th September 2021) - Tao, Yubo; Liu, Mengmeng; Han, Wenjia; Li, Peng
Abstract: Developing 3D printable waste paper based biocomposites is a potentially greener alternative to traditional waste paper recycling methods. In this paper, waste office paper (WOP) filled polylactide acid (PLA) biocomposites were prepared as filaments for Fused Filament Fabrication (FFF). The morphology, rheology, thermal properties, and physical properties of PLA-WOP composites were investigated. Results revealed that the addition of WOP improved the composites' melt flow abilities. The T g and T m of composites remained similar to the neat PLA. However, tensile strengths of the prints decreased with the increase of WOP content, which could be attributed to the heterogeneous dispersion and aggregation caused by the abundance of WOP in the system. When 5% WOP was used, the elongation at break increased in comparison with pure PLA specimens. Nonetheless, when the WOP content was increased to 15%, the elongation at break decreased. To improve the mechanical properties of the prints, a silane coupling agent (γ-methacryloxypropyltrimethoxylsilane, KH570) was used to modify WOP granules. The mechanical properties were clearly enhanced post KH570 treatment. Furthermore, FTIR analyses demonstrated that the hydrogen bonding improved interfacial adhesion between WOP fillers and the PLA matrix. Thermal decomposition showed that the PLA-WOP composites had virtually no degradation below 260 °C, indicating that the composite filaments are safe for indoor 3D printing.